Evasion of Classical Complement Pathway Activation on Plasmodium falciparum-Infected Erythrocytes Opsonized by PfEMP1-Specific IgG - Larsen, Mads Delbo; Quintana, Maria del Pilar; Ditlev, Sisse Bolm; Bayarri-Olmos, Rafael; Ofori, Michael Fokuo; Hviid, Lars; Garred, Peter (Frontiers in Immunology, 2019)
Members of the PfEMP1 protein family are expressed on the surface of P. falciparum-infected erythrocytes (IEs), where they contribute to the pathogenesis of malaria and are important targets of acquired immunity. Although the PfEMP1-specific antibody response is dominated by the opsonizing and complement-fixing subclasses IgG1 and IgG3, activation of the classical complement pathway by antibody-opsonized IEs does not appear to be a major immune effector mechanism. To study the molecular background for this, we used ELISA and flow cytometry to assess activation of the classical component pathway by recombinant and native PfEMP1 antigen opsonized by polyclonal and monoclonal PfEMP1-specific human IgG. Polyclonal IgG specific for VAR2CSA-type PfEMP1 purified from a pool of human immune plasma efficiently activated the classical complement pathway when bound to recombinant PfEMP1 in ELISA. In contrast, no activation of complement could be detected by flow cytometry when the same IgG preparation was used to opsonize IEs expressing the corresponding native PfEMP1 antigen. After engineering of a VAR2CSA-specific monoclonal antibody to facilitate its on-target hexamerization, complement activation was detectable in an ELISA optimized for uniform orientation of the immobilized antigen. In contrast, the antibody remained unable to activate complement when bound to native VAR2CSA on IEs. Our data suggest that the display of PfEMP1 proteins on IEs is optimized to prevent activation of the classical complement pathway, and thus represents a hitherto unappreciated parasite strategy to evade acquired immunity to malaria.